1996
DOI: 10.1164/ajrccm.153.2.8564126
|View full text |Cite
|
Sign up to set email alerts
|

A computer program using BALF-analysis results as a diagnostic tool in interstitial lung diseases.

Abstract: Recently, we showed that it is possible to distinguish between three common interstitial lung diseases (ILD) with similarities in clinical presentation by using a number of selected variables derived from bronchoalveolar lavage fluid (BALF) analysis. The aim of this study was to develop a more general discriminant model, based on polychotomous logistic regression analysis. The 277 patients involved in the study belonged to diagnostic groups with sarcoidosis (n = 193), extrinsic allergic alveolitis (EAA; n = 39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
1
6

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 19 publications
3
52
1
6
Order By: Relevance
“…They also highlighted that in sarcoidosis the majority of cases have an increased number of lymphocytes and a normal number of eosinophils/neutrophils and in severe cases the number of neutrophils can be increased as well. 62 The cell discrimination findings of BALF in the present study were revealed the predominance of lymphocytic plus neutrophilic and lone lymphocytic alveolitis.…”
Section: Resultssupporting
confidence: 57%
“…They also highlighted that in sarcoidosis the majority of cases have an increased number of lymphocytes and a normal number of eosinophils/neutrophils and in severe cases the number of neutrophils can be increased as well. 62 The cell discrimination findings of BALF in the present study were revealed the predominance of lymphocytic plus neutrophilic and lone lymphocytic alveolitis.…”
Section: Resultssupporting
confidence: 57%
“…They found a positive predictive value of 92.2% and negative predictive value of 97.1% for BAL cell differential in diagnosing sarcoidosis, and then applied computerassisted analysis of BAL findings (excluding lymphocyte subset analysis) to a similar patient population with a high degree of accuracy [41]. CHECK et al [26] generated likelihood ratios based upon relative percentage of lymphocytes in BAL from a database of 208 patients with BAL cellular differential analyses, and provided this information to clinicians evaluating patients for sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Again, haemodialysis was required. BALF analysis revealed a total cell amount of 35.3×10 4 cells·mL -1 ; (reference value for smokers 29.2± 3.3×10 4 cells·mL -1 ), with a predominance of neutrophils (89.4%; reference value for smokers 1.2±1.6%) [10]. Again, serum LDH was increased (2160 U·L -1 ; fig.…”
Section: Case Studymentioning
confidence: 91%